Comparison of the influence of some stand structural parameters on black pine seedling density and growth - Köseoğlu, Emirhan; Kara, Ferhat (Turkish Journal of Forestry, 2019)
Due to the difficulties in natural regeneration of black pine (Pinus nigra Arnold) forests, the influences of different stand structural parameters on regeneration success should be well understood. Canopy closure is one of the most commonly used parameters in natural regeneration activities in Turkey. However, studies regarding the effects of stand basal area (GYA) (m2/ha), stand stocking (%) and light transmittance (GIM) (%) on black pine regeneration has been limited. In this study, we aimed to determine the influences of GYA, stand stocking and GIM on seedling density, as well as root-collar diameter (KBÇ) and height of 5-year old black pine seedlings. We also aimed to find which parameter has more influence on black pine seedlings. GYA for each study plot installed within Kastamonu Araç Forest Planning Unit was calculated, and GIM of each plot was also determined using a Plant Canopy Imager. Stand stocking of each plot was calculated using a published equation. There were significant relationships between stand parameters and seedling density, KBÇ and seedling height (p<0.05). Moreover, GIM has more influence than GYA and stand stocking on seedling density, KBÇ and seedling height. Findings suggest that stand stocking and direct light measurements should be complementary to the commonly used canopy closure in black pine regeneration.
Keywords: meşcere stoğu; basal area; stand stocking; göğüs yüzeyi; regeneration; Forestry; SD1-669.5; par; gençleştirme; 15. Life on land